Separation and investigation of structure-mobility relationship of gonadotropin-releasing hormones by capillary zone electrophoresis in conventional and isoelectric acidic background electrolytes - Solínová, Veronika; Kasicka, Václav; Sázelová, Petra; Barth, Tomislav; Miksík, Ivan (Journal of chromatography. A, 2007)
Capillary zone electrophoresis (CZE) has been applied to qualitative and quantitative analysis, separation and physicochemical characterization of synthetic gonadotropin-releasing hormones (GnRHs) and their analogs and fragments. Structurally related peptides were separated in conventional and isoelectric acidic background electrolytes (BGEs), pH 2.18-2.50. Best separation was achieved in isoelectric BGE composed of 200 mM iminodiacetic acid, pH 2.32. The effective electrophoretic mobilities, m(ep), of GnRHs in five BGEs were determined and four semiempirical models correlating effective mobility with charge, q, and relative molecular mass, M(r), (m(ep) versus q/M(r)(k), where k is related to the molecular shape) were tested to describe the migration behavior of GnRHs in CZE. None of the models was found to be quite definitively applicable for the whole set of 10 GnRHs differing in size (tetrapeptide-decapeptide) and positive charge (0.91-3.00 elementary charges). Nevertheless, for the dependence of m(ep) on q/M(r)(k), the highest coefficient of correlation, R=0.995-0.999, was obtained for k close to the value 0.5 in all five acidic BGEs. This indicates that the most probable structure of GnRHs in these BGEs can be predicted as a random coil.
Keywords: Isoelectric Focusing; hormon uvolňující gonadotropiny; isoelektrická fokusace; Electrolytes; Gonadotropin-Releasing Hormone; elektrolyty; peptidy; Electrophoresis, Capillary; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; Peptides; elektroforéza kapilární